2016
DOI: 10.1177/1753193416669262
|View full text |Cite
|
Sign up to set email alerts
|

Perforator-based propeller flaps reliability in upper extremity soft tissue reconstruction: a systematic review

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 44 publications
3
21
0
1
Order By: Relevance
“…reported that the complication rate for propeller flaps in upper extremities was 24%, including PN (7%) and CN (3%). 30 These results are similar to our findings. When comparing complication rates for propeller flaps in lower extremities, our findings show lower rates than the results reported by Bekara et al, who concluded that the rate of complications was 25.2%, including PN (10.2%) and CN (3.5%).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…reported that the complication rate for propeller flaps in upper extremities was 24%, including PN (7%) and CN (3%). 30 These results are similar to our findings. When comparing complication rates for propeller flaps in lower extremities, our findings show lower rates than the results reported by Bekara et al, who concluded that the rate of complications was 25.2%, including PN (10.2%) and CN (3.5%).…”
Section: Discussionsupporting
confidence: 93%
“…Vitse et al . reported that the complication rate for propeller flaps in upper extremities was 24%, including PN (7%) and CN (3%) . These results are similar to our findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In these instances, free tissue transfer is required to provide adequate soft tissue coverage. Many types of skin flaps can be used as an option for wound coverage [1,2].…”
Section: Introductionmentioning
confidence: 99%